Investigating Effects of Interactive Virtual Reality Games and Gender on Immersion, Empathy and Behavior Into Environmental Education - Chiang, Tosti Hsu-Cheng (Frontiers in Psychology, 2021)
Environmental concerns are obstacles that all humans should confront. Accordingly, Taiwan has incorporated environmental education into its curriculum guidelines; however, difficulties have been encountered in its implementation because Taiwanese society clings to the concept of credentialism, students cannot focus in class, and course content is too abstract. Virtual reality (VR) techniques have been incorporated into the field of education for years; because they can increase the interestingness of learning and also concretely present matters through gamification, the present study applied VR techniques to resolve the aforementioned difficulties. VR can build environments and situations that would be impossible to visit in the real world, e.g. travel inside a human body, or the physically impossible—the surface of Mars. The aim was to increase students’ immersion in class would generate empathy toward the natural environment and perform actual behaviors to protect it. In terms of the experimental design, gender and teaching methods were defined as independent variables, and observation and questionnaires were conducted and applied to examine students’ immersion, empathy, and behaviors after learning. Participants in the experimental group watched a 3D video through a semi-immersive VR device, whereas those in the control group watched an ordinary video accompanied by an explanation from the teacher. The numbers of male and female students were equally allocated, and the learning outcomes of the two groups were further examined. A two-way multivariate analysis of variance test was conducted to examine the influences of 2(genders)×2(teaching methods) on students’ immersion, empathy, and actual behaviors and also mainly to inspect whether the differences between genders and teaching methods resulted in a direct influence or interaction. The experimental results revealed that the effectiveness of the application of VR techniques is affected by gender; female students presented more favorable performance in both empathy and actual behaviors. In brief, VR techniques can generally enhance students’ learning outcomes; however, limitations such as the cost of VR devices and material designs should also be considered.